Dietary Habits and Self-Reported Health Measures Among Norwegian Adults Adhering to Plant-Based Diets - Groufh-Jacobsen, Synne; Bahr Bugge, Annechen; Morseth, Marianne Sandsmark; Pedersen, Julia Tsuruta; Henjum, Sigrun (Frontiers in Nutrition, 2022)
Background As plant-based diets is increasing, we aimed to investigate dietary habits, dietary motivation and self-reported health of Norwegian adults who adhere to different types of plant-based diets. Methods In 2020, 808 subjects (530 women and 278 men) participated in an online survey, including vegans (8%), lacto-ovo vegetarians (16%), pescatarians (23%), and flexitarians (53%). Results Half of the participants reported to consume fruits daily, three quarters consumed vegetables daily, and one quarter consumed whole grain products daily. Half of the participants reported weekly consumption of sweets and salted snacks, and 10% reported daily consumption of sugary drinks. Daily consumption of milk and dairy substitutes were reported by vegans (49%), lacto-ovo vegetarians (33%), pescatarians (32%), and flexitarians (25%). Daily consumption of meat replacement products was reported by vegans (3%), lacto-ovo vegetarians (5%), pescatarians (2%). Reported supplement use was highest among vegans (62%) and lowest among flexitarians (28%). Dietary motivations were driven by environmental (71%), health (64%), and animal welfare (49%) concerns, across all dietary groups. 75% reported their self-perceived health to be good or very good. Conclusion We found that Norwegian adults adhering to plant-based diets consumed less fruit, vegetables, and whole grain products, together with more sugar than recommended in the Norwegian dietary guidelines. The participants reported their self-perceived health to be good or very good.